Adolescent Reading Literacy in View of Family Support and Reading Duration in Middle School Students - Firdausih, Andrielina; Utami, Cahyaning Bhakti; Fitri, Ilhamda (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Literacy is an important skill and relates to the ability to listen, speak, write, and count. This study aims to analyze the influence of family support and duration of reading on adolescent reading literacy. This study uses a quantitative survey approach research design. The number of samples in this study were 127 students through cluster random sampling method. Data analysis was carried out in several stages, namely data coding, SPSS analysis, namely inference test, normality test, correlation test, and multiple linear regression test. The results showed that the dominant (36.2%) subjects were 14 years old. As many as (30.7%) are 15 years old. The results showed that half (50%) of the research subjects read books for entertainment several times a year. The results showed that the majority (68%) of the study subjects had moderate reading duration and the family support given to the sample was very high (93%). The results of the study also show that family support and duration of reading affect adolescent reading literacy. The result of this study have implications for parent mindset to support literacy from an early age and adolescent to read more frequently.